Identification of adipose tissue transcriptomic memory of anorexia nervosa - Rizaldy C. Zapata; Chanond A. Nasamran; Daisy R. Chilin-Fuentes; Stephanie C. Dulawa; Olivia Osborn (BMC, 2023)
Abstract Background Anorexia nervosa (AN) is a complex debilitating disease characterized by intense fear of weight gain and excessive exercise. It is the deadliest of any psychiatric disorder with a high rate of recidivism, yet its pathophysiology is unclear. The Activity-Based Anorexia (ABA) paradigm is a widely accepted mouse model of AN that recapitulates hypophagia and hyperactivity despite reduced body weight, however, not the chronicity. Methods Here, we modified the prototypical ABA paradigm to increase the time to lose 25% of baseline body weight from less than 7 days to more than 2 weeks. We used this paradigm to identify persistently altered genes after weight restoration that represent a transcriptomic memory of under-nutrition and may contribute to AN relapse using RNA sequencing. We focused on adipose tissue as it was identified as a major location of transcriptomic memory of over-nutririon. Results We identified 300 dysregulated genes that were refractory to weight restroration after ABA, including Calm2 and Vps13d, which could be potential global regulators of transcriptomic memory in both chronic over- and under-nutrition. Conclusion We demonstrated the presence of peristent changes in the adipose tissue transcriptome in the ABA mice after weight restoration. Despite being on the opposite spectrum of weight perturbations, majority of the transcriptomic memory genes of under- and over-nutrition did not overlap, suggestive of the different mechanisms involved in these extreme nutritional statuses.